2023
DOI: 10.48550/arxiv.2303.04938
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cosmic muon flux attenuation methods for superconducting qubit experiments

Abstract: We propose and demonstrate two mitigation methods to attenuate the cosmic muon flux compatible with experiments involving superconducting qubits. Using a specifically-built cosmic muon detector, we find that chips oriented towards the horizon compared to chips looking at the sky overhead experience a decrease of a factor 1.6 of muon counts at the surface. Then, we identify shielded shallow underground sites, ubiquitous in urban environments, where significant additional attenuation, up to a factor 35 for 100-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…As an example, the cryogenic facility at the Laboratori Nazionali del Gran Sasso (LNGS), in Italy, which is covered by a rock overburden of 1.4 km, provides a reduction factor of about 1 million for the muon flux [26], [27]. Nonetheless, as shown in [8], effective suppression factors can also be achieved in shallower sites (up to a factor of 35 for depths of 100 meter). Fig.…”
Section: The Case Of Cosmic-ray Muonsmentioning
confidence: 99%
See 2 more Smart Citations
“…As an example, the cryogenic facility at the Laboratori Nazionali del Gran Sasso (LNGS), in Italy, which is covered by a rock overburden of 1.4 km, provides a reduction factor of about 1 million for the muon flux [26], [27]. Nonetheless, as shown in [8], effective suppression factors can also be achieved in shallower sites (up to a factor of 35 for depths of 100 meter). Fig.…”
Section: The Case Of Cosmic-ray Muonsmentioning
confidence: 99%
“…While environmental radioactivity can be mitigated by using dedicated shielding and radio-pure materials in the proximity of the qubits, benefiting from the experience of the scientific community developing low-radioactivity detectors for Particle Physics, cosmic-ray muons cannot be easily suppressed. Interesting studies have shown that shallow underground sites can provide good attenuation factors, ranging from 2 to a factor of 35 for depths of 10 meters and 100 meters, respectively [8]. In addition, it has been demonstrated in [8] using a specificallybuilt cosmic muon detector that, by orienting chips towards the horizon, the muon flux above-ground can be reduced by a factor of 1.6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation